Issues in public enterprises / edited by R. S. Nigam - "Nigam , R. S. (ed.)" (Delhi, 1980)
The second half of the twentieth century has witnessed active interest and direct participation of governments in economic activities. This has been necessitated on account of limits upto which the private enterpreneurs can marshall resources for long term development and socially oriented projects. Moreover, the concept of basic responsibilities of governments has also under gone a rapid change from that of custodian of rule of law to one of 'custodian of vital socio-economic interests' on account of increased emphasis on welfarism.
Keywords: Govt business enterprises